2020
DOI: 10.3389/fvets.2020.563762
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tail-Biting and Intestinal Microbiota Composition in Pigs

Abstract: Tail-biting (TB) in pigs is a serious behavioral disorder. It is an important challenge in swine production as it impacts animal welfare and health and the economics and safety of the pork meat supply chain. To prevent TB, approaches including enrichment material and tail docking are proposed but none are optimal. Nutrition appears to be an important factor in TB behavior, perhaps by modulating the intestinal microbiota (IM). Our aim was to assess the association between TB behavior and IM in pigs through comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…In agreement with the study by Rabhi et al 27 , we identified taxa differences between biter pigs and controls. Rabhi et al, reported lower Lactobacillus in the biter pigs, and a similar reduction in the abundance of Lactobacillus has also been reported in feather pecking hens 58 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with the study by Rabhi et al 27 , we identified taxa differences between biter pigs and controls. Rabhi et al, reported lower Lactobacillus in the biter pigs, and a similar reduction in the abundance of Lactobacillus has also been reported in feather pecking hens 58 .…”
Section: Discussionsupporting
confidence: 93%
“…The higher relative abundance of Firmicutes in the tail biter pigs was primarily driven by the higher abundance of the families Lachnospiraceae, Ruminococcaceae and Clostridiales Family XIII. Our results are partly in line with the so far only published paper on gut microbiota composition and tail biting in pigs 27 . In line with their results, we also found the highest similarity in microbiota composition between the biters and the victims and the largest differences between biters and controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, Li et al, recently reported that the human intestinal bacterial community was significantly disturbed by the combinatorial colistin and amoxicillin (a broad-spectrum beta-lactamase antimicrobial) exposure, illustrating that this combinatorial antibiotic exposure, which may have an impact on several different intestinal bacterial families, could lead to long-term effects on the bacterial diversity of a simulated human intestinal microbiota as well as an increase in the relative abundance of opportunistic pathogens within this microbiota [ 52 ]. Likewise, it was reported that the oral administration of broad-spectrum antimicrobials (e.g., amoxicillin, chlortetracycline) in clinically healthy pigs was associated with a significant alteration in the composition of the fecal microbiota of the treated animals [ 24 , 53 ].…”
Section: Discussionmentioning
confidence: 99%